Linguagem e mediação no design de um curso on-line - Pasini, Tatiana Higa (2008)
Set in the context of the distance education, this research investigated the process of combining elements of design of an online course components. The analyzed course was Teachers Links: Reflexão e Desenvolvimento para professores de inglês, a course for English teachers. This course has gone through a process of redesigning and a new component was included, the Reflection component, considering the reflective teacher practices. Since then, considering this new component, questions have arisen about the content being established, the component development, the team responsible for its development and also about the existence of an articulation between the new component and the component which already existed, the Development component. From these concerns, this study has chosen to discuss the process of articulating the design elements in the tow components, as the component Reflection was planned after the Development component and the Reflection had to adapt to it so that the final design outcome was consistent and harmonious. The elements of design investigated in both components were: a) the language used in the pages of the course; due to the fact the language materializes the relations between the teacher and the student and the relations between the designer and the student, b) the mediation strategies and c) the design itself, the components planning. These elements were analyzed in the units of each component; each unit is made up by 5 activities. In order to substantiate the analysis, the theoretical concepts in this study are the Systemic-Functional Linguistics (Halliday, 1985), the mediation concept proposed by Vygotsky (1929/1998a, 1934/1998b) and the concepts of design proposed by Reigeluth (1999), Nielsen (2000), Collins (2003) and by Filatro (2004). As a result of this research, it was noted that the Development and the Reflection components have the design elements really well articulated, coherent and harmonious, fruit of a team work that shares the same ideal for the online courses